Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1152/ajprenal.1994.266.1.f46
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of endothelin activation of phospholipase A2 in rat renal medullary interstitial cells

Abstract: Previous studies from this laboratory have demonstrated that endothelin-1 (ET) stimulates phosphatidylinositol (PI) hydrolysis, activates dihydropyridine-insensitive Ca2+ channels, and promotes prostaglandin E2 (PGE2) accumulation in cultured rat renal medullary interstitial cells (RMIC). The mechanism whereby ET augments PGE2 production was explored in the current study. ET-evoked PGE2 accumulation proceeded independent of large increments in cytosolic free Ca2+ concentration ([Ca2+]i), derived from either ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…3,7,9 Actions of ET-1, via ET A and ET B receptors, include phospholipase A 2 stimulation and the resultant increase in arachidonic acid-derived mediators. 1,7,15,21 Previous studies have investigated the involvement of CYP450 hydroxylase and COX metabolites in the renal vasoconstrictor response to ET-1. 7,9,10,16, 22 Oyekan et al, using in vitro and in vivo techniques, have shown that the CYP450 hydroxylase pathway contributes to the ET-1-evoked decrease in renal blood flow, but the role of the COX pathway appears to be complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,7,9 Actions of ET-1, via ET A and ET B receptors, include phospholipase A 2 stimulation and the resultant increase in arachidonic acid-derived mediators. 1,7,15,21 Previous studies have investigated the involvement of CYP450 hydroxylase and COX metabolites in the renal vasoconstrictor response to ET-1. 7,9,10,16, 22 Oyekan et al, using in vitro and in vivo techniques, have shown that the CYP450 hydroxylase pathway contributes to the ET-1-evoked decrease in renal blood flow, but the role of the COX pathway appears to be complex.…”
Section: Discussionmentioning
confidence: 99%
“…Second messengers responsible for the ET-1-mediated vascular response include phospholipase C activation and subsequent calcium mobilization from intracellular stores, as well as phospholipase A 2 stimulation, resulting in production of arachidonic acid metabolites. 1,14,21,25 In freshly isolated smooth muscle cells from large-caliber renal vessels, Gordienko et al 25 demonstrated that ET-1-induced mobilization of intracellular calcium was accompanied by membrane depolarization. ET-1 also stimulated Ca 2ϩ -activated K ϩ channels in renal vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunocytochemical staining for CD21 was carried out on acetone-fixed, 5-µm isopentane-liquid nitrogen frozen sections according to a procedure adapted from methods described previously by this laboratory (21). Optimal dilutions of the first antibody, determined by checkerboard titration, were incubated with the tissue at room temperature for 60-90 minutes followed by 3 rinses in buffered saline at 3°-5°C.…”
mentioning
confidence: 99%
“…ET-1 induced the phosphorylation of cPLA 2 at ser505 in KCs from BDL and sham animals; however, the effect was significantly greater in KCs from BDL animals. In other cell types, ET-1 has been demonstrated to activate cPLA 2 and the release of various eicosanoids including TXA 2 , via binding to Gq/G11 and Gi coupled ET (A) and ET (B) receptors, subsequently inducing the activation of ERK1/2 or p38 MAPK through PLC or PKC mediated signaling pathways (38,39,41,42,44,45,47,(55)(56)(57)(58)(59)(60)(61). Therefore, the purposes of the present study were to delineate the signaling pathways induced via stimulation of Gq/G11 and Gi coupled ETBRs and the relative roles of intermediates in the activation of cPLA 2 and production of TXA 2 in KCs in response to ET-1, and determine whether the hepatic stress of early stage fibrosis alters the signaling pathways through modifications in the expressions or activities of signaling intermediates.…”
Section: Discussionmentioning
confidence: 99%